Pengaruh Inovasi Produk, Kualitas Produk dan Harga Terhadap Keputusan Pembelian pada CV. Pia Forta Kota Probolinggo - Moh Saivi Saifur Rizal; Ngatimun Ngatimun; Setyani Hidayati (Universitas Panca Marga, 2024)
This research was conducted at CV. Pia Forta Probolinggo City with research objectives to be achieved is to determine the effect of Product Innovation, Product Quality and Price on Purchasing Decisions partially on CV. Pia Forta Probolinggo City. The population in this study were consumers who visited using estimated purchase in the previous few months, namely: February to April 2023 as many as 192 consumers. While the researcher was conducting the research, the samples taken were as many as 64 respondents using the incidental sampling technique. The type of research used in this research is descriptive quantitative research, the variables used include Product Innovation, Product Quality, Price and Purchase Decision. The method of data analiysis from the results of this study is a quantitative descriptive method using statistics in the from of instrument tests, normality tests, classical assumption tests, multiple regression analysis, multiple correlation coefficients, cofficients of determination and partial hypothesis testing (t test). The results of the study are shown by the results of the partial hypothetical test that has been carried out with a significance level of 5%, it can be concluded that 1) Product Innovation with a tcount value of 2.201 is greater than a ttable of 1.670. 2) Product Quality with tcount value is 3.514 greater than ttable 1.670. 3) Prices with a tcount value are 3.408 greater than the 1.670 ttable.